Mediumship seen by some pioneers of mental health (Archives of Clinical Psychiatry, 2004)
Experiences regarded as mediumistic have been found in most civilizations and have exerted an important influence over the societies. Despite few academic studies nowadays, mediumship was a subject of serious investigations by some Psychiatry and Psychology pioneers. Research developed by Janet, James, Myers, Freud and Jung concerning mediumship was revised, two points were stressed: its causes and its relations with psychopathology. These researchers had come to three distinct conclusions. Janet and Freud associated mediumship with psychopathology and an exclusive origin in the personal unconscious; Jung and James accepted the possibility of a non-pathological aspect of mediumship and an origin in the personal unconscious, but without definitively excluding the actuation of a discarnate spirit. Finally, Myers saw mediumship as a higher development of the personality, having as its causes a combination of the unconscious, telepathy and the action of discarnate spirits. The authors argue the need to become acquainted with the studies already done in order to resume these investigations in search of a really scientific paradigm about mediumship.